Community Economic Empowerment With Maize Cultivation In Nagari Tuik Iv Koto Mudiek, Batang Kapas District, South Coast Regency: Pemberdayaan Ekonomi Masyarakat Dengan Budidaya Jagung Di Nagari Tuik Iv Koto Mudiek Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Yonny Arita Taher; Afrida Afrida; Yulfi Desi; Bustari Badal; Inawaty Sidabalok; Asnurita; Meriati (Journal of Community Service and Application of Science, 2022)
The community service carried out by the Ekasakti Padang University Team is in the Nagari Tuik area, Batang Kapas District. the northern part of the South Coast District. The community, in general, is farming, because the agricultural land is very large, namely 256 ha. There are still many people who cultivate rice fields, but not many have cultivated corn which further increases income. Because the base price of corn is more stable than the base price of grain. The base price of flat corn alone is between Rp. 2500 – Rp. 5000 a kilo. In addition, corn can be processed into various products such as steamed brownies made from corn and sweet corn pudding. This service socializes the cultivation of sweet corn plants and their processing so that they can increase people's income and increase knowledge about corn cultivation. Knowledge increased from 24.6% to 80.6%. And people's income also increased with the production of steamed brownies with a selling price per unit of Rp. 2,500. BEP will be achieved only when 123 pieces are produced. So if it is produced more than that, it has already benefited. With this sweet corn cultivation program, it can be a community empowerment program